Root and leaf anatomy of some terrestrial representatives of the Cranichideae tribe (Orchidaceae) - de Cássia Andreota, Rita [UNESP] (2015)
The Orquidaceae family has more than 25,000 species, of which 20 % are terrestrial Cranichideae mainly belonging to the tribe, which is inserted in Orchidoideae, one of the five subfamilies of the Orchidaceae. This group of terrestrial orchids presents a confusing taxonomy and is a poorly known group in terms of their vegetative anatomy in opposition to the epiphytic representatives that have been extensively investigated. This paper describes the root and leaf anatomy of ten species of Cranichideae tribe found in Brazil, belonging to subtribes Cranichidinae, Goodyerinae, and Spiranthinae, comparing their organization to those of the epiphytic plants. We also point out some features that can be useful for the characterization of each subtribe. The roots have studied characteristics that may assist in the absorption and retention of water as the occurrence of velamen and exodermis system, and in the presence of tilossomos Cranichidinae and Spiranthinae. The leaves are narrow with a homogeneous mesophyll, covered by uniseriate epidermis and covered by thin cuticle. The xylem cells are arranged in pairs or inverted V-shape, as in the other orchids Cranichideae tribe.